Aplikasi Metode Proses Hirarki Analitik dan Pemrograman Integer 0-1 Dalam Menentukan Komposisi Pemain Sepak Bola pada Football Manager 2019 - Christoper Aryo Pambudi; Benny Yong; Taufik Limansyah (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2022)
Football has became a favorite sport of the world community. Every supporter of a football team would want their team to win the competition they participated in. Formation, strategy, and composition of teams are factors that influence the team's victory in a match. These three factors are the responsibility of a football coach in concocting his team in winning. This paper will discuss the application of the Analytical Hierarchy Process and the Integer 0-1 Program to assist football coaches in composing the composition of football players in a match. The AHP is used in this case to calculate the priority weights of each soccer player criteria while the Integer 0-1 Program is used to get eleven players to be deployed in a match. The results of both methods are simulated using the game Football Manager 2019 with team Manchester United in the English Premier League. Based on simulations conducted during the two season matches, Manchester United was able to finish in a fairly stable ranking in the English Premier League standings for two seasons.